Rawer than raw [compact disc] - Rush, Bobby (Deep Rush Records, 2020)
Bobby Rush pays homage to the great bluesmen from Mississippi on his 27th studio album. This is Bobby Rush, stripped-down; just his guitar, harmonica, singing, and foot tapping. There's a song from Skip James, Robert Johnson, Sonny Boy Williamson, Willie Dixon, and Howlin' Wolf. One song is Public Domain originally recorded for the Library of Congress by Alan Lomax, but later made famous by Muddy Waters.